Efficacy of Tramadol vs Pethidine for Control of Anaesthesia Induced Shivering in Patients undergoing Elective Caesarian Section under Spinal Anaesthesia - Ali, Syed Asad; Khan, Muhammad Ahmed; Akram, Sumera; Ibrahim, Hassan; Mahmood, Arif; Ali, Akhtar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the effectiveness of tramadol for control of Anaesthesia Induced Shivering and compare it with pethidine in elective caesarian section patients under spinal anaesthesia.Study Design: Quasi-experimental studyPlace and Duration of Study: Main Operation Theatre, SKBZ/ Combined Military Hospital, Rawalakot Pakistan, from Jan to Jun 2020.Methodology: After approval from the ethical review committee of the Hospital and taking patient’s informed consent, 60 patients who developed grade 2 or 3 shivering after induction of spinal anesthesia were allocated to two group A & group B alternatively. Group A received IV tramadol 1mg/kg whereas Group B received IV pethidine 0.5mg/kg. SPSS version 21 was used to analyze the data and calculate mean and standard.Results: Anaesthesia induced shivering was effectively controlled in 86.66% (n=26) participants in Tramadol Group versus 83.33% (n=25) participants in Pethidine Group, p-value was calculated as 0.0001 which was significant.Conclusion: Tramadol is an acceptable, easily available, as well as a safer alternative to pethidine for control of anaesthesia induced shivering in patients having elective caesarean section under spinal anaesthesia.